MOLECULAR DOCKING STUDIES OF 1, 2 DISUBSTITUTED IDOPYRANOSE FROM VITEX NEGUNDO WITH ANTI-DIABETIC ACTIVITY OF TYPE 2 DIABETES - PAPPU SRINIVASAN; ARUMUGAM SUDHA; RAMAR MANIKANDAN; CHINNASAMY ARULVASU (International Journal of Pharma and Bio Sciences, 2011)
Type 2 diabetes is one of the major life threatening diseases worldwide these cases are progressing at an incremental rate every year and number of research works are going on to control the disease by targeting its enzymes or proteins. The medicinal properties of Vitex negundo and one of its compounds, 1, 2 disubstituted idopyranose (C23H28O12) was checked against diabetes mellitus by molecular docking with various proteins which are involved in the carbohydrate metabolism. The inhibitor, 1, 2 disubstituted idopyranose was found to be increased insulin sensitivity and normalize blood glucose level by binding in the active sites of the protein and thus useful therapeutic agent for the herbal therapy of diabetes. The docking method to explore the ability of 1, 2 disubstituted idopyranose bound to the active binding site in the proteins and showed that the inhibitor is the best binder of the present study. We concluded that the natural products with interesting biological properties and structural diversity have often served as valuable lead drug candidates for the treatment of human diseases and also it replaces the chemically synthesized drugs which cause side effects.